2001
DOI: 10.1084/jem.193.9.1015
|View full text |Cite
|
Sign up to set email alerts
|

The Tprk Protein of Treponema pallidum Is Periplasmic and Is Not a Target of Opsonic Antibody or Protective Immunity

Abstract: The finding that Treponema pallidum, the syphilis spirochete, contains 12 orthologs of the Treponema denticola outer membrane major sheath protein has engendered speculation that members of this T. pallidum repeat (Tpr) family may be similarly surface exposed. In this regard, the TprK protein was reported to be a target of opsonic antibody and protective immunity and subject to immunologically driven sequence variation. Despite these findings, results from our previous analyses of treponemal outer membranes in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
94
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(99 citation statements)
references
References 36 publications
5
94
0
Order By: Relevance
“…Preliminary studies based on semiquantitative reverse transcription-PCR of the Nichols strain (3) showed a preponderance of tprK mRNA over the other tpr genes during early experimental infection (day 10), suggesting the modulation of tpr expression. This result was partially confirmed by densitometric analysis after limiting-dilution reverse transcription-PCR (12), which also showed that not all of the tpr genes are equally transcribed, although no preponderance of tprK message was found. Transcription modulation is also sup-ported by a recent study based on microarray and real-time PCR (20), which showed the tpr genes to be differentially expressed with respect to TP0426 (V-type ATPase, A1 subunit) in the Nichols strain.…”
supporting
confidence: 63%
See 1 more Smart Citation
“…Preliminary studies based on semiquantitative reverse transcription-PCR of the Nichols strain (3) showed a preponderance of tprK mRNA over the other tpr genes during early experimental infection (day 10), suggesting the modulation of tpr expression. This result was partially confirmed by densitometric analysis after limiting-dilution reverse transcription-PCR (12), which also showed that not all of the tpr genes are equally transcribed, although no preponderance of tprK message was found. Transcription modulation is also sup-ported by a recent study based on microarray and real-time PCR (20), which showed the tpr genes to be differentially expressed with respect to TP0426 (V-type ATPase, A1 subunit) in the Nichols strain.…”
supporting
confidence: 63%
“…Although the function of the Tprs is still unknown and attempts to determine the cellular location of TprI and TprK have resulted in controversial results (10,12), several studies have highlighted the importance of these antigens during the immune response to syphilis in the rabbit model (17,19,22). Immunization with recombinant peptides based on TprI, TprF, and TprK sequences significantly alters lesion development after intradermal challenge (3,10,22); moreover, TprK possesses multiple alleles in T. pallidum isolates, conferring an impressive potential for antigenic variation and, consequently, of immune evasion (4,5).…”
mentioning
confidence: 99%
“…This T. pallidum gene family exhibits heterogeneity among different subspecies and strains, indicative of recombination events among the different tpr alleles (27). In addition, protective immune responses and generation of opsonic activity against Tpr proteins has been reported (28) but disputed (29). T. denticola possesses only 'a single member (TDE0405, major outer sheath protein) related to this gene family, suggesting that this family has been specifically expanded in the T. pallidum lineage.…”
Section: Resultsmentioning
confidence: 99%
“…The diversity in the humoral response is probably not due to TprK variation in these studies, because the peptides are homologous to the Seattle Nichols laboratory strain that was used to infect the rabbits. Unlike most T. pallidum isolates that have heterogeneous TprK sequences within an isolate, the laboratory Nichols strain seems to have only one TprK sequence (8,10,11). In separate experiments groups of rabbits were infected, and serial sera were collected from each animal.…”
Section: Discussionmentioning
confidence: 99%
“…We have reported that when one member of this family, Treponema pallidum repeat protein K (TprK), is used as an immunogen, lesion development is attenuated following homologous challenge in the rabbit model (7). Although Hazlett et al (10) failed to corroborate these results, we have confirmed and expanded the original results to show that immunizing with the N-terminal portion (aa 37-273) of TprK retards lesion development (manuscript in preparation) as previously seen with a larger fragment (aa 37-348) (7). Therefore, there is evidence that TprK does play an important role in the immune response.…”
mentioning
confidence: 99%